2014
DOI: 10.1016/j.cell.2014.05.051
|View full text |Cite|
|
Sign up to set email alerts
|

p53-Dependent Nestin Regulation Links Tumor Suppression to Cellular Plasticity in Liver Cancer

Abstract: Summary The p53 tumor suppressor coordinates a series of anti-proliferative responses that restrict the expansion of malignant cells and, as a consequence, p53 is lost or mutated in the majority of human cancers. Here, we show that p53 restricts expression of the stem and progenitor cell-associated protein nestin in an Sp1/3 transcription factor-dependent manner and that nestin is required for tumor initiation in vivo. Moreover, loss of p53 facilitates dedifferentiation of mature hepatocytes into nestin-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 57 publications
5
143
0
Order By: Relevance
“…9c). As Nestin is also a well-described mediator of stemness and plasticity in the liver (Tschaharganeh et al 2014), this further supports that the SASP can induce stem cell properties in surrounding tissue.…”
Section: Resultsmentioning
confidence: 56%
“…9c). As Nestin is also a well-described mediator of stemness and plasticity in the liver (Tschaharganeh et al 2014), this further supports that the SASP can induce stem cell properties in surrounding tissue.…”
Section: Resultsmentioning
confidence: 56%
“…Although a subset of HCCs is thought to arise from hepatic progenitor cells (HPCs), most HCCs arise from differentiated hepatocytes (Tschaharganeh et al 2014;Marquardt et al 2015). The PK isoform expression of HPCs is unknown; however, differentiated hepatocytes do not express PKM2 (Supplemental Fig.…”
Section: Since Pkm2mentioning
confidence: 99%
“…P21 (WAF1) binds to the G1-S/CDK (CDK1, CDK2 and CDK4/6) complexes (responsible for the G1/S transition in the cell cycle) inhibiting their activity. Many studies demonstrated that the activation of p21 might be due to a p53-dependent pathway (37) and p21 has been shown to be essential for p53-mediated G1/S boundary cell-cycle arrest and cellular senescence triggered by DNA damage (38).…”
Section: Apoptosis Led By Cell Cycle Arrest: Importance Of P53 and P21mentioning
confidence: 99%